The choosing aspect of consciousness - Spohr, Julia C. (My University, 1906)
Introduction: To introduce the subject we must have some idea of what consciousness is. To be conscious is to think, to think is to put together impressions and ideas and in order to do this we must be the subject of internal changes. These internal changes in turn are caused by surrounding things. For instance place an organism in the midst of some objects. If it is influenced by them it can know or think nothing of them. Their existence can only be revealed by the effects they produce upon it. So with our lives we are influenced by the world about us and especially our associates. Incessant change however is not the sole thing needed to produce consciousness, for if these so called changes are at random, we have no consciousness. Analysing these thoughts we may formulate a working definition by saying that, "Consciousness is an orderly succession of changes combined and arrayed in special ways. "If note be taken of the different states as they occur, if they pass through consciousness simply as images pass over a mirror there can be no intelligence until these states are classified. To choose certain states of consciousness is not an easy ask for on the contrary it is the choosing wherein lies the difficulty. We are all here to fulfil some task or mission and cannot afford to go out of our volition until the last item of our duty fulfilled. There is one word that means so much to us, and it is that word "suggestion." No man knows what hour will bring to him a suggestion that may change the whole course of his life or how does it happen that one is a merchant, another a doctor, a third, a lawyer, etc. Our environments influence us largely. Were it not for our reasoning or our will suggestion would be absolute in its power and control. Suggestion therefore is an instrument of great and subtle power and one to be handled with care.
Citation: Spohr, Julia C. The choosing aspect of consciousness. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Psychology; Consciousness; Theses